Negotiating Conservative Traditions and Religious Moderation: A Sociological Study of the Construction of Social Harmony in Pesantren in Madura - Supandi Supandi; Kurratul Aini; Abdul Hobir (LPPPM STAI Darul Hikmah Bangkalan, 2026)
The purpose of this research is to analyze the role of pesantren in internalizing the values of religious moderation through the system applied in education organized with the pesantren's tradition. This research uses a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews, participatory observations, and documentation studies involving kiai, ustadz, and students in the pesantren environment. Data analysis was carried out using thematic analysis techniques through the stages of data reduction, data presentation, and conclusions drawn, and strengthened by triangulation of sources and techniques to ensure the validity of findings. The results of the study show that the internalization of religious moderation in Pesantren occurs holistically through the integration of formal curriculum, curriculum (formal and hidden curriculum), and Pesantren traditions. The example of kiai and ustadz as well as the collective culture of pesantren has proven to be a key factor in shaping the religious attitude of students that is moderate, inclusive, and oriented towards social harmony. This study concludes that pesantren function as a foundation of moderate Islamic education that is effective in maintaining social cohesion in a multicultural society. The implications of this study emphasize the importance of strengthening the role of Pesantren in the development of Islamic education policies and practices oriented towards religious moderation and social peace.